The Boy Allies under Two Flags - Hayes, Clair W. (Clair Wallace), 1887- (Salt Lake City, UT : Project Gutenberg, 2004)
"The Boy Allies under Two Flags" by Clair W. Hayes is a historical novel written in the late 19th century. The story focuses on the adventures of two young boys, Jack Templeton and Frank Chadwick, who are navigating the tumultuous waters of World War I while serving on the British scout cruiser, H.M.S. Sylph. As they face enemy attacks and participate in naval battles, the boys find themselves deeply entrenched in the war$1 (Bs excitement and dangers. At the start of the narrative, we are introduced to H.M.S. Sylph and its commander, Lord Hastings, as they engage in battle against German cruisers in the Mediterranean Sea. The opening chapters depict a fierce naval skirmish, showcasing the bravery and quick-thinking of Jack and Frank as they work alongside the crew during the conflict. After successfully wounding the enemy, the Sylph is forced to turn back upon realizing their adversaries are too formidable. This encounter sets the scene for character development, highlighting the boys' camaraderie and shared ambition for action and adventure, while also introducing the historical context of the naval battles of World War I that will shape their journey ahead. (This is an automatically generated summary.)s
Release date is 2004-08-01
Produced by Sean Pobuda
Keywords: World War, 1914-1918 -- Naval operations -- Juvenile fiction